Poetry Reading: Activities of ordering and sequencing questions in Elementary School (INTERFACES DA EDUCAÇÃO, 2025)
The objective of this study is to present and discuss the theoretical-methodological proposalof ordering and sequencing of poetry reading questions in Elementary School, in order to contribute tothe studies on the teaching and learning of Portuguese, both in reading skills and in written textualproduction. The work is based on the concepts of reading, with emphasis on the studies of AppliedLinguistics and the practice of ordering and sequencing reading, pointing out the relevance of thisproposal as part of the student's development process, as a reader and a writer at school. In preparingthe proposal, the following are considered: (I) the survey of the main ideas of the text; (II) the elaborationof a text from those ideas; (III) the creation of reading questions based on the listed ideas; (IV) thestudent-reader’s production of a text as a replica/counterword based on the answers given. From theelaboration of the proposal for ordering and sequencing the questions, the results indicate: (a) theidentification of main ideas of the text; (b) the student's position on the theme of the text; (c) theproduction of text as a replica/counterword as a result of the whole process.